Ethnobotany of Traditional Children’s Games of Javanese Society in Central Java: ETNOBOTANI PERMAINAN TRADISIONAL ANAK-ANAK MASYARAKAT JAWA DI JAWA TENGAH - Sulistijorini; Dafi Al Anshory (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Traditional games are using simple tools and materials, such as plants. The aim of this study is to count the percentage of traditional games using plants that still exist in Central Java Province, to analyze the role of plants on traditional game, and to reveal the children’s knowledges about plants from traditional games. The data were collected by interviewing the respondents, including the parents (>50 y.o), the adults (15-30 y.o), the childrens (5-14 y.o) in 4 study areas: the hillside of Lawu, the hinterlands of Karangpandan, the ruralside of Karanganyar, and the city of Surakarta. The results showed that the precentage of traditional games that still exist are: in the hillside (39%), the hinterland (28%), the rural (19%), the city (14%). Plant usage in traditional games by the children has a tendency to use cultivated plants, which grow in home gardens and the parts of plants that are often used are leaves. Plant availaibility could strongly influence the existence of traditional games in society. Childrens have knowledge about plantsthat are obtained or developed through playing traditional games. Keywords: children’s knowledge, plants, play, the hillside, the city